Wage and Price Setting in Macedonia: Evidence from Survey Data - Gani Ramadani; Nikola Naumovski (National Bank of the Republic of Macedonia, 2015)
This paper presents the main findings of a survey on wage and price formation of firms in Macedonia conducted in the first half of 2014. The main objective was to identify some relevant characteristics about the dynamics of wages and prices in Macedonia, clarifying the relationship between them, and to draw some conclusions on firms' response to various adverse shocks in adjusting labour costs, prices and their various components. The most important conclusions are that: i) wages tend to remain unchanged longer than prices; ii) the most significant factor producing frequent wage adjustment is tenure rather than inflation; iii) time concentration of wage and price changes is significantly lower in Macedonia than in the surveyed EU countries as a result of the considerably low automatic indexation of wages and large share of firms that operate in highly price competitive pressures; iv) downward nominal wage rigidity could be considered relatively high associated with the extent of permanent contracts, and is more important compared to the low downward real wage rigidity; v) there is a weak price-wage link which corresponds with inflation being the least important factor driving wage changes; and vi) in case of adverse shocks firms tend to adjust costs and prices rather than margins and output.
Keywords: D21; E30; J31; 330; survey data; wage and price setting; wage rigidity; indexation; Macedonia